Evaluation of Rat Alveolar Bone Response to Angelus MTA or Experimental Light-cured Mineral Trioxide Aggregate Using Fluorochromes - Gomes Filho, João Eduardo [UNESP]; Teixeira de Moraes Costa, Mariana Machado [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Tobias Duarte, Paulo Carvalho [UNESP]; Takamiya, Aline Satie [UNESP]; Lodi, Carolina Simonetti [UNESP]; Bernabé, Pedro Felício Estrada [UNESP] (Elsevier B.V., 2011)
Introduction: The aim of this study was to evaluate the rat alveolar bone response after the implantation of experimental light-cured mineral trioxide aggregate (MTA) or Angelus MTA (Angelus, Londrina, Parana, Brazil) by histological and fluorescence analysis. Methods: Thirty Wistar Albino rats were divided into three groups. In the control group, empty polyethylene tubes were inserted into the rat alveolar sockets immediately after extraction. In the other groups, the tubes were filled with light-cured MTA or Angelus MTA. Five animals from each group were injected with calcein on day 7, alizarin on day 14, and oxytetracycline on day 21. on day 30, these animals were killed, and the right hemimaxillas were removed and histologically processed. Half of the maxillas were processed and stained with hematoxylin and eosin. The remaining maxillas were processed for fluorescence analysis and stained with Stevenel blue and alizarin red. New bone was histomorphometrically evaluated using a Merz grid. Results: The light-cured MTA presented a similar response when compared with Angelus MTA; it was characterized by a mild inflammatory response and complete bone healing. In the light-cured MTA group, the fluorescence areas were more evident at 21 days, showing an increase in bone formation. However, dystrophic mineralization was observed only with Angelus MTA. Conclusions: It was concluded that both materials present a similar inflammatory response and bone healing, but dystrophic mineralization was observed only with Angelus MTA. (J Endod 2011;37:250-254)
Keywords: Biocompatibility; fluorochromes; inflammation; mineral trioxide aggregate